Maquiavel defensor da liberdade - Di Sarno, Ivani Cunha (2006)
The innovative and provocative Machiavelli lures us toward dianoésis and the practice of logos. Gradually, the study aims to show the objective rationality of this philosopher who favored freedom of political action over the pragmatism of individual men as the only way to establish public political power and foster concepts of freedom in the political realm. The word freedoms appears in the Discorsi as the beginning and end of all politics in the republican form of government and, by extension, guarantees the continuation of the regime itself. The basis of freedom is when, under the same constitution, the Prince, ruling class and the power of the people are united, and each of the three branches checks and balances the others. 2 The constitutional recourse of contesting decisions made by any one of these three branches by the other two is how freedom is established. In each step of this thesis, the understanding of political freedom according to Machiavelli is based on two important foundations. The first, discord among the ruling class and the oppressed and the second foundation, the distancing of the idea of freedom from the humanistic one of ideal regimes. When Discorsi is examined, the differences that make up the reference point and, from various angles, these fundamentals, are present in the eras (Greek and Roman) that the author reports. This is the key to understanding the Florentine philosopher s position on the humanists, who believed that conflict paralyzed city life and led it into decadence and consequently toward the suppression of freedom. Basically, the Machiavellian thesis can be summed up as: if in each city there were always two opposing factions, two humors, two contrary and opposite forces, one the optimized desire to dominate the people, and the other, the desire of the people to not be dominated, the duty of the legislator is to understand the logic of the situation: not to extinguish one humor on behalf of the other, but to confer on both appropriate access to public space and the whole of society and government. This is the guarantee of freedom. Although the topics addressed in this study vary, there is a concern to unify: that true political freedom should oppose submission of the common good to private interests, as demonstrated by the defender of freedom